The Deconstruction of Orientalism in Lisa See's Shanghai Girls in the Perspective of Discourse Analysis - Hu Yinfeng (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Shanghai Girls, one of the masterpieces of contemporary Chinese American writer Lisa See, tells the story of two sisters who travel from Shanghai, China to live in Chinatown in the United States over a period of 20 years, depicting China and Chinese immigrants in a turbulent historical era. This study aims to explain the deconstruction of "Orientalism" in the novel by using discourse analysis: exemplifying and analyzing the use of words closely related to Chinese people and culture. The results of the study not only confirm the close connection between the novel's themes and Chinese culture and history, but also show Lisa's intention to counter "Orientalism" in her writing. Through my study of Shanghai Girl, I argue that the Chinese history and culture represented in Lisa See's novel reflect a mixture of an American writer's Chinese writing and personal experiences. Although only one-eighth Chinese, Lisa is passionate about Chinese history and culture. All the narratives about Chinese history and culture in the novel do not come from the author's uncritical imagination, but from the collection and research of a great deal of historical information. Lisa tries to use her language to describe the inner world of the characters as meticulously as possible, presenting an image of China that is different from the stereotypical, mysterious and demonized Orientalism.